Kajian Teknis Sistem Penyaliran Pada Penambangan Batu Granit Di PT. Hansindo Mineral Persada - Sutrisno, Hendri; Meilasari, Fitriana; Ichwanudin, Rachmat (Jurnal Lingkungan dan Bencana Geologi, 2024)
Mining at PT. Hansindo Mineral Persada uses the quarry method. This type of mining will produce a basin at the mining site. The basin formed is used as a sump or water reservoir. The sump functions as a reservoir for water entering the mine. If the incoming water exceeds the maximum sump due to high rainfall, it will have an impact on the mining site. The increased discharge of runoff entering the sump will potentially cause inundation or flooding on the mining ground floor. Based on these problems, it is necessary to analyze the drainage system to overcome water problems at PT. Hansindo Mineral Persada. The purpose of this study is to determine the amount of incoming runoff discharge, the shape and dimensions of the channel according to the needs of the company. The method used in this study is a quantitative method with an empirical approach. The method used to calculate the planned rainfall is the Gumbel method and the method for determining the area of the catchment area is the polygon method. The data used are rainfall data for the last 10 years to determine planned rainfall and topography data to obtain catchment areas, as well as water flow patterns in mining areas to obtain runoff discharge. The obtained runoff discharge is used to design open channel shapes. Based on the analysis that has been carried out, it is obtained that the runoff discharge entering the sump is 0.4916m3/s. The larger the area of the catchment area, the greater the runoff discharge that enters the sump, so that the recommended cross-section of the open channel is in the form of a trapezoid with dimensions (yn = 0.612m), (b = 0.7m), (α = 60°), and (s = 0.25%).